Exploring The Role of Duolingo in Elevating University Students’ Writing Skills - Martinis Yamin; Nisaul Fadillah; Nurul Faizah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to (1) find out the comparisonof students' writing skills before and after using theDuolingo application and (2) find out theadvantages and disadvantages of students whenusing the Duolingo application. This research usesmixed methods. Data collection techniques includetests, interviews, and documentation methods. The test was carried out in two stages, namely pre-testand post-test. Interview informants were selectedusing purposive sampling techniques. Data were processed using descriptive statistics and Miles Huberman analysis. The research was conductedon 10 English Literature students at UIN Sulthan Thaha Saifuddin Jambi. The research results showthat based on the results, Duolingo's role canimprove students' writing skills. This can be seenbased on the results of the post-test carried out bystudents. In the post-test assessment, allparticipants obtained higher scores that exceededthe mean. The highest score on the post-test was 95 and the lowest score was 80. There were nostudents below the completeness score and 10 students above the completeness score. Then theaverage post-test score was 89.5. Meanwhile, otherresearch results show that the advantages anddisadvantages of using the Duolingo applicationcan be seen in the interview results. In terms ofadvantages, students believe that Duolingo canimprove their writing skills because there are lotsof features such as flashcards, translations, quizzes, listening sections, exercises, and others. Meanwhile, the disadvantage of using theDuolingo application is that this application takesup a lot of memory space on the cellphone whenthe user uses it all the time, especially when itreaches a high level or unit.